Civic Organizations in Vietnam's One-Party State: Supporters of Authoritarian Rule? - Jörg Wischermann (German Institute of Global and Area Studies (GIGA), 2013)
Associationalism under authoritarian rule is not automatically a good thing. The empirical findings laid out in this article indicate that authoritarian dispositions and practices are prevalent in all types of Vietnamese civic organizations, at least as far as internal decisionmaking processes are concerned. As is the case in most countries of Southeast Asia, old as well as new ideas of the state and state traditions have a strong impact on the patterns of authoritarianism found in Vietnamese civic organizations. From the empirical findings, it might be concluded that Vietnamese civic organizations support authoritarian rule - though the extent of such support varies; this has generally been an underresearched question. This pioneering article seeks to stimulate further research by offering new insights into how authoritarian power is exercised in Vietnam by addressing how associations' activities stabilize rules, how the associated legitimizing effects can be conceptualized and understood in theoretical terms, and what would be a suitable operationalization of the aforementioned concepts.
Keywords: 300; civil society; authoritarianism; authoritarian rule; Vietnam